Non-alignment strategy: politics and theory - Цебенко, Олег; Шимчук, Олександр; Tsebenko, Oleh; Shymchuk, Oleksandr (Lviv Politechnic Publishing House, 2018)
Досліджено політику неприєднання як одину з ключових стратегій діяльності держави у міжнародних відносинах. Проаналізовано основні теоретичні та методологічні підходи дослідження політики неприєднання, виокремлено дефініції цього поняття та виявлено ключові ознаки стратегії не приєднання держав. Простежено історичний аспект виникнення ідеї руху неприєднання. Досліджено вплив глобалізації на зміну політики неприєднання та нейтралітету держав. Члени Руху неприєднання зобов’язані, як зазначено в Гаванській декларації 1979 року, забезпечити національну незалежність, суверенітет, територіальну цілісність та безпеку країн, що не приєдналися “до їх” боротьби проти імперіалізму, колоніалізму, неоколоніалізму, расизму та всіх форм зовнішньої агресії, окупації, панування, втручання або гегемонії, а також проти політики великої держави та блоку. Політика неприєднання вимагає від держави, яка слідує за її принципами реалізації зовнішньополітичних намірів, спрямованих на поділ світу на два ворожі блоки. Декларуючи статус неприєднання статусу, держава передусім стежить за внутрішніми чинниками, економічними або політичними, та зовнішніми чинниками, тобто сильною економічною незалежністю, можливістю зовнішньополітичного або військового тиску. Крім того, курс на неприєднання є можливим лише за відсутності будь-яких очевидних або прихованих територіальних претензій до держави, яка прагне проводити політику неприєднання. Беручи до уваги реалізації статусу неприєднання, держава краще базується на досвіді європейських вже неприєднаних держав, а також сьогодні міжнародній ситуації. Однак сучасні умови дещо змінюють концепцію неприєднання.

The complex study of the state non-alignment strategy is done. The theoretical and methodological basis of nonalignment strategy is analyzed, the problem of definition this phenomenon is investigated, the main aspects of neutrality strategy tendencies are clarified. The historical aspects of non-alignment policies are developed. The Non-alignment Movement members were obliged as stated in the Havana Declaration of 1979 to ensure the national independence, sovereignty, territorial integrity and security of non-aligned countries “in their” struggle against imperialism, colonialism, neo-colonialism, racism, and all forms of foreign aggression, occupation, domination, interference or hegemony as well as against great power and bloc politics. A policy of non-alignment required from a state that follows its principles implementation of foreign policy intentions aiming to overcome the world’s partition into two hostile blocs. Declaring a non-aligned status a state first of all followed internal causes, that are economical or political calamities, and external motives, that is strong economic dependence, possibility for foreign policy or military pressure. Furthermore, a course for non-alignment is only possible for lack of any evident or implemented territorial claims to a state that aims to pursue a politics of non-alignment. Taking into account a process of the implementation of a non-aligned status, a state had better rely on the experience of the European already non-aligned states as well as today’s international situation. Yet, modern conditions somewhat modify the concept of non-alignment. One can argue, but nowadays, for instance an expression “abstention form permanent alignment with blocs” might sound somewhat weird and with some ideological hue. A word “bloc” is considered anachronism in the modern dictionary of international relations, it rather an echo of the Cold War times; therefore, nonalignment as the concept has to be tied down to modern time and be able to deal with modern definitions.
Стратегія неприєднання: політика й теорія
Keywords: неприєднання; нейтралітет; стратегія; безпека; глобалзація; non-alignment; neutrality; strategy; security; globalization; 327.8